Gender Gaps in Competition: New Experimental Evidence from UK Professionals - Sophie Clot; Marina Della Giusta; Giovanni Razzu (Institute of Labor Economics (IZA), 2020)
We use a controlled experiment widely adopted in the literature to assess the extent of gender differences in attitudes towards competition in a sample of UK professionals working in two different companies. We find no gender differences in attitudes towards competition nor in performance under a competitive reward scheme. This results qualifies the findings of a large number of experimental studies that show that women are more likely than men to shy away from competition. We also find that, in our sample of professionals, women's performance under competitive schemes does not decline. We conclude that it is important to avoid generalisations on the presence of gender gaps in attitudes towards competition. This being the first field study with professional workers in relatively competitive sectors, we think more needs to be carried out.
Keywords: C93; J16; J71; 330; gender; competition; field experiment